2020
DOI: 10.1016/j.ebiom.2020.103060
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of MMR prediction model based on simplified clinicopathological features and serum tumour markers

Abstract: Background Although simplified clinicopathological features and serum tumour markers (STMs) were reported to be associated with the status of mismatch repair (MMR) in colorectal cancer (CRC) patients, their predictive value alone or in combination for MMR status remains unknown. Methods A retrospective analysis of 3274 participants with MMR testing and STMs measurements from two institutions was conducted. The prediction model was developed in the primary cohort that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In previous studies, [ 5 ] we analyzed clinicopathological data of 3274 participants from two institutions and assessed their predictive value in patients of all ages with CRC. We found that a columnar line graph created using simple clinicopathological indicators was able to accurately predict the status of MMR/MSI in patients with an AUC value of 0.754 (95% CI: 0.715–0.793) in the validation group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, [ 5 ] we analyzed clinicopathological data of 3274 participants from two institutions and assessed their predictive value in patients of all ages with CRC. We found that a columnar line graph created using simple clinicopathological indicators was able to accurately predict the status of MMR/MSI in patients with an AUC value of 0.754 (95% CI: 0.715–0.793) in the validation group.…”
Section: Discussionmentioning
confidence: 99%
“…Molecularly targeted therapies and chemotherapeutic agents are used to treat patients with dMMR CRC [ 4 ]. Recently, a growing body of evidence suggests that the individual treatment response of patients with CRC is strongly related to its molecular characteristics [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have already built a simple model to predict the mismatch repair status of colorectal cancer patients based on clinicopathological parameters and tumour markers with good results in the previous phase. (5) This time, we will further focus on whether the machine learning approach is more effective than the conventional predictive model by constructing four machine learning models and a traditional logistic regression based on simple clinicopathological indicators.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Recently, a growing body of evidence suggests that the individual treatment response of CRC patients is strongly related to its molecular characteristics. (5) Microsatellite instability (MSI) is the abnormal shortening or lengthening of 1-6 repeat base pair units of DNA, which is caused by inactivation of the DNA MMR system. (3,6,7) Colorectal cancer patients with microsatellite instability are more likely to nd Lynch syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous prognostic factors utilizing peripheral biochemical biomarkers have been validated (4)(5)(6). Dysregulated lipid levels have been consistently linked to the occurrence, risk, and progression of CRC.…”
Section: Introductionmentioning
confidence: 99%